ASSOCIATION OF PARASITE INFECTED HIV/AIDS PATIENTS WITH 〖CD〗_4^+ COUNT IN BENIN CITY, NIGERIA. - S. A. AIGBODION; C. E. OKAKA; N. O. EGHAFONA; F. AIGBODION; A.D. OTORO (African Journal of Health, Safety and Environment, 2026)
In many developing countries, including Nigeria, a range of parasitic organisms have been identified as significant contributors to illness in people living with HIV. This study examined the link between parasitic infections and cell counts among HIV-positive and HIV-negative individuals attending Specialist and Faith Mediplex Hospitals, Benin City. Samples of blood, stool, and skin snips were collected from 2,000 participants. Blood samples were tested to determine HIV status, cell counts, and blood-borne parasites. HIV diagnosis was conducted using the ELISA method, with positive results further verified through Western blot analysis. The study revealed that male (77.2%) and female (82.7%) had equal (χ² =0.189) risk of contracting HIV infection. The ratio of HIV positive (18.1%) to negative (7.5%) patient count was 2:1 in ≤ 200 and 1:1 for > 200. HIV status was dependent (χ² =5.037) of count. Eight intestinal parasites (prevalence), Ascaris lumbricoides (8.1%), Cryptosporidium spp. (12.4%), Entamoeba histolytica (8.4%), Giardia lamblia (0.6%), Hookworm (5.1%), Isospora belli (20.1%), Microsporidium spp. (7.3%), Strongyloides stercoralis (6.2%), two blood parasites – Plasmodium falciparum (43.1%), Wuchereria bancrofti (5.4%), and one tissue parasite – Onchocerea volvulus (8.6%), were recorded in HIV patients. Plasmodium falciparum emerged as the most frequently detected parasite in the study, followed by Isospora belli. An association was found between cell count and the occurrence of P. falciparum (χ² = 7.599), I. belli (χ² = 7.540), Microsporidium species (χ² = 1940.598), and Giardia lamblia (χ² = 4.500). Hence, can be used as indicator for the presence of HIV/AIDS.